Chronic cough: a disorder of response inhibition?. Issue 5 (2nd May 2019) - Mazzone, Stuart B.
Many physicians will agree that chronic cough can be difficult to control and, for some patients, disease-modifying therapies fail to alleviate their cough. This is a condition now commonly referred to as refractory chronic cough and is present in a significant number of people in the community [1, 2]. Our understanding of the mechanisms of cough has expanded dramatically in recent years [3], but it wasn't all that long ago when suggestions were rife that refractory chronic cough was a condition more likely "in the patient's head" than pathobiological in nature. Although the acceptance of refractory chronic cough as a real clinical entity is now well established, a study reported by Cho et al. [4], published in this issue of the European Respiratory Journal, suggests that we may need to revisit the notion that the problem resides in the brain, but not for the reasons once propagated. The findings of Cho and co-workers suggest that chronic cough involves an imbalance between the level of peripheral drives that induce cough and the central mechanisms that are engaged to suppress cough http://ow.ly/tU1w30o9vBT